2021
DOI: 10.1590/s1678-3921.pab2021.v56.02544
|View full text |Cite
|
Sign up to set email alerts
|

Increment in eucalyptus diameter as affected by seasonality and production system

Abstract: The objective of this work was to assess the current monthly increment in diameter of eucalyptus (Eucalyptus grandis x Eucalyptus urophylla) trees in response to different production systems, climatic factors, and thinning. The trees were evaluated in four production systems: monoculture and crop-forestry, livestock-forestry, and crop-livestock-forestry integration. The increment in diameter of 80 trees was measured monthly from May 2015 to May 2019. The effect of the climatic variables was determined through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
0
2
1
Order By: Relevance
“…Such situation had probably ensured to the eucalyptus trees a non-limiting water availability through the most part of the experimental period and this favorable water balance may had contributed to suppress the relevance of the intra-annual air temperature fluctuation. Therefore, this result was different from those found at the northern Mato Grosso by Tonini et al (2021), since there the authors observed a not so strong, but relevant negative correlation between mean daily air temperature and eucalyptus diameter growth. The results found by us can be endorsed by those found by Ryan et al (2020).…”
Section: Relation Between Diameter Growth and Climate Variablescontrasting
confidence: 88%
See 2 more Smart Citations
“…Such situation had probably ensured to the eucalyptus trees a non-limiting water availability through the most part of the experimental period and this favorable water balance may had contributed to suppress the relevance of the intra-annual air temperature fluctuation. Therefore, this result was different from those found at the northern Mato Grosso by Tonini et al (2021), since there the authors observed a not so strong, but relevant negative correlation between mean daily air temperature and eucalyptus diameter growth. The results found by us can be endorsed by those found by Ryan et al (2020).…”
Section: Relation Between Diameter Growth and Climate Variablescontrasting
confidence: 88%
“…According to the same authors, the mean annual air temperature across the sites was only relevant in situations where water availability was not guaranteed (rainfed). The studied sites had mean annual temperatures varying from 19.4 to 25.7 °C and the authors concluded that, for water limiting conditions, the annual increment in biomass was reduced by the increase in temperature across the sites, like the negative correlation found by Tonini et al (2021).…”
Section: Relation Between Diameter Growth and Climate Variablesmentioning
confidence: 83%
See 1 more Smart Citation